Activities of the dorsolateral and medial prefrontal cortices during oral function training with cognitive training elements: a NIRS study - Masumi Abe; Rui Nouchi; Toru Ogawa; Naru Shiraishi; Hiroki Hihara; Keiichi Sasaki; Nobuhiro Yoda (BMC Oral Health, 2024)
Abstract Background Cognitive function plays a crucial role in human life, and its maintenance and improvement are essential in both young and older adults. Since cognitive decline can be associated with oral function decline, preventing the decline in both cognitive and oral functions is an urgent social issue. Several training methods to improve each function have been proposed. Previous studies have indicated that greater brain activity during training is associated with increased benefits for cognitive function. Although adding cognitive function elements to oral function training may promote the activation of brain activity during oral function training, the effects have not been validated. The main purpose of this study is to develop a novel training program that combines oral function training with cognitive training, which is expected to activate key brain regions involved in oral and cognitive functions, such as the left dorsolateral prefrontal cortex (DLPFC) and right medial prefrontal cortex (mPFC). Methods Four types of training programs combining oral and cognitive training: PaTaKaRa × calculation, lip exercise × N-back, tongue exercise × inhibition, and tongue exercise × memory, were developed. Each program had seven levels of difficulty [level 0 (no cognitive load) and level 6 (maximum difficulty)]. Twelve healthy young adults participated in the study and were instructed to perform all four programs. Brain activity in the left DLPFC and right mPFC were measured during each training session using two-channel near-infrared spectroscopy (NIRS). Results No significant brain activity was observed during training at level 0. Brain activity in the left DLPFC was significantly increased at levels 1 and 2 and in the left DLPFC and right mPFC at level 6 during PaTaKaRa × calculation training. Brain activity in the left DLPFC was significantly increased at level 6 during tongue exercise × inhibition training. Brain activity in the left DLPFC and right mPFC was significantly increased at level 6 during lip exercise × N-back training. Conclusion Oral function training did not significantly increase brain activity; nevertheless, oral function with cognitive training stimulated brain activity in the prefrontal cortex. Trial registration : UMIN-CTR. ID: UMIN000039678. date: 06/03/2020.